PENGARUH PROFITABILITAS, GROWTH, KEBIJAKAN HUTANG DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KEBIJAKAN DIVIDEN - Novianti, Zulfa Eka Widya; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe purpose of this research is to examine the influence of profitability variable which is measured by return on assets (ROA), growth is measured by using total assets (GRT), debt policy is measured by debt to equity ratio (DER), institutional ownership is measured by (INST), and dividend policy is measured by dividend payout ratio (DPR). The population is all consumer goods industrial sector manufacturing companies which are listed in Indonesia Stock Exchange. The data has been obtained from www.idx.co.id and STIESIA Indonesia Stock Exchange Corner. 13 sample companies have been selected as sample by using purposive sampling technique with the criteria industrial manufacturing companies which are listed in Indonesia Stock Exchange in 2012-2015 periods. The predictive ability of profitability, growth, debt policy, institutional ownership to the DPR is 54.9% as it is described by the magnitude of adjusted R-square is 0.549 or 54.9%, whereas the remaining 45.1% is influenced by other factors which are not included in the research model. The result of the research shows that profitability (ROA) and debt policy (DER) does not give any influence to the DPR. Growth, in this research, gives negative influence to the DPR and institutional ownership gives positive influence to the DPR.Keywords: Profitability, growth, debt policy, institutional ownership, dividend policy